Визначення напруженого стану навколо отворів в циліндричній оболонці із композитного матеріалу - Богатирчук, Анатолій Степанович; Романенко, Вікторія Миколаївна (НТУ "ХПІ", 2017)
Розглядається розрахунок напружено-деформованого стану циліндричної оболонки з двома круговими отворами з композитного матеріалу, який вважається ортотропним. Для такого класу задач приймаються гіпотеза прямих ліній Тимошенка. Для розвязку застосовуємо метод скінченних елементів. Результати досліджень можуть бути використані в різноманітних галузях техніки, зокрема в хімічній та харчовій промисловості

We consider the calculation of stress-strain state of the cylindrical shell with two circular halls of composite material, which is orthotropic. For this class of problems the hypothesis of the straight line for the whole shell package and Tymoshenko kinematic hypothesis are accepted, according to them initially normal to the coordinate plane the shell element after deformation remains straight but not perpendicular to the surface of the deformed coordinate without changing its length. The finite-element method is applied for solution. The result of the investigation is the algorithm of the stress-strain state of cylindrical shells with holes , made of orthotropic material. Also this algorithm was created in the C ++ language and specific numerical results were obtained with using this algorithm. As a scientific innovation the problem for calculation of the stress-strain state in the orthotropic shell with holes using the finite-element method was formulated and solved. The practical significance of the developed method of such problems calculation is that the research results can be used in various fields of technology, particularly in the chemical and food industries.
Determination of the stress state around holes in a cylindrical shell made of a composite material
Keywords: оболонка; круговий отвір; композитний матеріал; ортотропний матеріал; метод скінченних елементів; гіпотеза Тимошенка; напружений стан; деформація; ізопараметричний елемент; shell; circular hole; composite material; orthotropic material; finite-element method; Tymoshenko hypothesis; state of stress; deformation; isoperimetric element